THE IMPLEMENTATION OF DOMESTICATION STRATEGY TO MAINTAIN BAHASAâS ROLE IN ADOPTING NOVEL TERMINOLOGIES FOR SCIEN-TECH UNDERTAKING - Mujiyanto, Yan (Language Circle: Journal of Language and Literature, 2015)
The advancement of science and technology (scien-tech) is always accompanied by creation of novel terminologies. The more a language is used as a means of conveying information on new findings the more the language is enriched with new meaning, be it represented in a form of borrowing, new invention, blend, coinage, or common words with new meaning. This has necessitated scien-tech stakeholders to face the challenge of whether to borrow through transliteration or to adopt as well as adapt such terminologies for the benefit of utilizing information to flow effectively. A problem that appears is how to provide counterparts of such terminologies considering that the supply of scien-tech terminologies in Bahasa is relatively limited compared to that in English while borrowing can be inappropriate or even misleading. This paper intends to explain a number of ways in which endeavors to provide tentative supplies of terminologies through domestication strategy have always been made for scien-tech adoption as well as adaptation to proceed appropriately while enhancing the role of Bahasa in maintaining its function to deal with scien-tech undertaking.